Impact of a digitized workflow for knee endoprothesis implantations on hospital-specific ratios - von Schudnat, Christian; Lahmann, Benjamin; Schoeneberg, Klaus-Peter; Albors-Garrigos, Jose; De-Miguel-Molina, María (Technology and health care, 2023)
BACKGROUND: The continuous decrease of healthcare resources requires hospitals to improve efficiency while striving to improve quality standards that deliver better patient outcomes. OBJECTIVE: The objective of this study was to analyze whether the implementation of digital support systems during orthopedic surgery positively affected clinical processes and quality ratios. METHODS: A retrospective case-control study of 297 knee joint replacement procedures was conducted between 2015 and 2020. Thirty-five patients were allocated to the treatment and control groups after they were identified with exact matching and estimation of the propensity score. Both groups were balanced regarding the selected covariates. The effect of the surgical procedure manager (SPM) on the incidence of acute haemorrhagic anaemia between the two groups was evaluated with a t-test, and the odds ratio was calculated. RESULTS: SPM-supported surgery has no significant influence on the incidence of acute haemorrhagic anaemia but leads to significantly shorter hospital stay (1.93 days), changeover (4.14 minutes) and recovery room time (20.20 minutes). In addition, it reduces the standard deviation of operation room times. CONCLUSIONS: The study concludes that SPM enhances surgical efficiency and maintains quality outcomes. To overcome their increasing financial pressure hospital management should commercially evaluate the implementation of digital support systems.
Keywords: Hospitals; digital technology; nemocnice; ortopedické výkony; efficiency; Quality improvement; surgical procedure manager; lidé; studie případů a kontrol; operating rooms; Workflow; zlepšení kvality; Quality Improvement; retrospektivní studie; Orthopedic Procedures; Case-Control Studies; the standard of care; Retrospective Studies; průběh práce; Humans